Education on diarrhea treatment from decoction of guava leaves at the LKSA Muawanah foundation - Deni Firmansyah; Sulistiorini Indriaty; Nur Rahmi Hidayati; Angelica Alma Sera; Destri Putri Ramadhanti (Universitas Muhammadiyah Magelang, 2022)
Diarrhea is a bowel movement (defecation) characterized by liquid or semi-liquid stools with a higher water content than usual. Microorganisms such as bacteria, viruses, and protozoa can cause diarrheal disease, depending on the etiology. A decoction of guava leaves is used in traditional medicine to treat diarrhea. The goal of the community service is to teach the LKSA Muawanah Foundation's foster children about diarrhea and how to treat it traditionally with boiled guava leaves. The definition of diarrhea, causes of diarrhea, prevention of diarrhea, treatment of diarrhea, distribution of brochures for prevention and treatment of diarrhea, games, post-test, and how to make anti-diarrhea drinks from guava leaf stew were all part of this program. Participants gain a better understanding of the causes of diarrhea, how to prevent it, and how to make traditional anti-diarrhea medicinal drinks from guava leaf stew, which is both cheaper and easier. The material presented is well understood by the participants, as evidenced by their ability to correctly answer ten questions during the post-test